Cardinality estimation using collective interference for large-scale RFID systems. (1st April 2017) - Park, Jonghoon; Moon, Cheoleun; Yeom, Ikjun; Kim, Yusung
Abstract: Estimating the number (cardinality) of Radio Frequency Identification (RFID) tags is a principal problem for large-scale RFID systems. This paper proposes a novel protocol for RFID cardinality estimation using synchronized response signals. For every estimation round, we need a single time-slot to parse multi-bit information from the synchronized signals that are concurrently transmitted from tags. Our protocol guarantees satisfaction of an arbitrary accuracy requirement within the smallest number of time-slots compared to existing estimation protocols. The efficiency of our protocol is based on two components: tags' synchronization and random number generation from a geometric distribution. We design these components to be feasible without heavy computation or memory overhead, and our protocol can be applied to low-cost and resource-constrained passive RFID tags. We have implemented a proof of concept prototype using software defined radio and programmable RFID tags. By conducting large-scale simulations, we have shown that our protocol outperforms the existing cardinality estimation protocols.